Innovation in economics, social and education: Industry 4.0 / Nazirul Mubin Mohd Noor and Maznah Wan Omar - Mohd Noor, Nazirul Mubin; Wan Omar, Maznah (Faculty of Business & Management, Universiti Teknologi MARA (UiTM) Cawangan Kedah, 2020)
Consumers are eager to improve their lives with connected devices. Smart connected devices are ringing in a new era for businesses, economics and educations. The interconnectivity of our digital devices that provide endless opportunities for businesses to listen and respond to the needs of the current and future customer, by sending the right message, at the right time, on the right devices. A systematic literature review method employed in surveying the related literature. Educational institution is moving forward to ensure the right skills embedded in the curriculum to p repare a marketable candidate for the future work force. The agenda of innovation in society, economics and education is the biggest springboard in moving forward with the revolution of Industry 4.0.